PENGARUH CO-BRANDING PADA NIAT BELI - Muhammad Iqbal; Waluyo Budi Atmoko; Sugiyarmasto Sugiyarmasto (Jurnal Bisnis dan Kewirausahaan, 2025)
Abstract This study aims to examine the effect of co-branding on purchase intention. Data were obtained through a laboratory experiment conducted at Setia Budi University in Surakarta. The experimental technique used 35 participants. Hypothesis testing used the Kolmogorov-Smirnov normal distribution test and paired sample test. The results indicate that co-branding advertising strengthens consumer purchase intention.